A Novel Educational Intervention: Improving Abdominal Pressure Strategies during Colonoscopy - Osborne, Kelly (My University, 2021)
Gastroenterology (endoscopy) procedures continue to increase in volume as innovative therapeutic endoscopy procedures are performed to meet the increasing demand for minimally invasive procedures. During endoscopy procedures, staff assists physicians with therapeutic techniques that require skill-specific training to ensure staff competency. Performing these therapeutic techniques often poses ergonomic challenges to staff related to patient positioning and repositioning, prolonged standing, leaning, and awkward body postures. The most common endoscopic procedure is screening, surveillance, and diagnostic colonoscopies. A typical therapeutic technique performed during a colonoscopy that is also an ergonomic challenge is manual abdominal pressure. Gastroenterologists frequently utilize abdominal pressure techniques to decrease colon movement and bowel looping to achieve a completed colonoscopy. Currently, there is a lack of standardization, education, and training on abdominal pressure strategies. Identifying, developing, and launching clinical staff training for endoscopy-specific therapeutic maneuvers is time-consuming and requires dedicated and educated clinicians. Without proper training, staff performing abdominal pressure techniques can cause injuries to patients and themselves with downstream adverse effects, including staff work culture and absenteeism, patient satisfaction, room utilization, and unit financial performance. The Doctorate of Nursing Practice project focused on developing an evidence-based interactive course to improve staff efficacy and confidence in the application of abdominal pressure strategies during colonoscopy procedures.
Keywords: abdominal pressure strategies, simulation training, endoscopy, patient safety, clinical staff competency assessment, safe patient handling